Observed trends in extreme temperature over the Klan - Ahmad Norazhar Mohd Yatim; Mohd Talib Latif; Fatimah Ahamad; Md Firoz Khan (ResearchGate, 2019)
This study investigates the recent extreme temperature trends across 19 stations in the Klang Valley, Malaysia, over the period 2006−16. Fourteen extreme index trends were analyzed using the Mann−Kendall non-parametric test, with Sen’s slope as a magnitude estimator. Generally, the annual daily mean temperature, daily mean maximum temperature, and daily mean minimum temperature in the Klang Valley increased significantly, by 0.07°C yr−1, 0.07°C yr−1 and 0.08°C yr−1 , respectively. For the warm temperature indices, the results indicated a significant upward trend for the annual maximum of maximum temperature, by 0.09°C yr−1, and the annual maximum of minimum temperature, by 0.11°C yr−1. The results for the total number of warm days and warm nights showed significant increasing trends of 5.02 d yr−1 and 6.92 d yr−1 , respectively. For the cold temperature indices, there were upward trends for the annual minimum of maximum temperature, by 0.09°C yr−1, and the annual minimum of minimum temperature, by 0.03°C yr−1, concurrent with the decreases in the total number cold days (TX10P), with −3.80 d yr−1, and cold nights (TN10P), with −4.33 d yr−1. The 34°C and 37°C summer days results showed significant upward trends of 4.10 d yr−1 and 0.25 d yr−1, respectively. Overall, these findings showed upward warming trends in the Klang Valley, with the minimum temperature rate increasing more than that of the maximum temperature, especially in urban areas.